The current role of laparoscopic resection for HCC: a systematic review of past ten years - Di Sandro, Stefano; Danieli, Maria; Ferla, Fabio; Lauterio, Andrea; De Carlis, Riccardo; Benuzzi, Laura; Buscemi, Vincenzo; Pezzoli, Isabella; De Carlis, Luciano (Translational Gastroenterology and Hepatology, 2018)
The use of laparoscopic liver resection (LLR) has progressively spread in the last 10 years. Several studies have shown the superiority of LLR to open liver resection (OLR) in term of perioperative outcomes. With this review, we aim to systematically assess short-term and long-term major outcomes in patients who underwent LLR for hepatocellular carcinoma (HCC) in order to illustrate the advantages of minimally invasive liver surgery. Through an advanced PubMed research, we selected all retrospective, prospective, and comparative clinical trials reporting short-term and long-term outcomes of any series of patients with diagnosis of HCC who underwent laparoscopic or robotic resection. Reviews, meta-analyses, or case reports were excluded. None of the patients included in this review has received a previous locoregional treatment for the same tumor nor has undergone a laparoscopic-assisted procedure. We considered morbidity and mortality for evaluation of major short-term outcomes, and overall survival (OS) and disease-free survival (DFS) for evaluation of long-term outcomes. A total of 1,501 patients from 17 retrospective studies were included, 15 studies compare LLR with OLR. Propensity-score matching (PSM) analysis was used in 11 studies (975 patients). The majority of the studies included patients with good liver function and a single HCC. Cirrhosis at pathology ranged from 33% to 100%. Overall mortality and morbidity ranges were 0–2.4% and 4.9–44% respectively, with most of the complications being Clavien-Dindo grade I or II (range: 3.9–23.3% vs. 0–9.52% for Clavien I–II and ≥ III respectively). The median blood loss ranged from 150 to 389 mL; the range of the median duration of surgery was 134–343 minutes. The maximum rate of conversion was 18.2%. The median duration of hospitalization ranged from 4 to 13 days. The ranges of overall survival rates at 1-, 3- and 5-year were 72.8–100%, 60.7–93.5% and 38–89.7% respectively. The ranges of disease free survival rates at 1-, 3- and 5-year were 45.5–91.5%, 20–72.2% and 19–67.8% respectively. The benefits of LLR in term of complication rate, blood loss, and duration of hospital stay make this procedure an advantageous alternative to OLR, especially for cirrhotic patients in whom the use of LLR reduces the risk of post-hepatectomy liver failure. The limits of LLR can be overcome by robotic surgery, which could therefore be preferred. Further benefits of minimally invasive surgery derive from its ability to reduce the formation of adhesions in view of a salvage liver transplant. In conclusion, the results of this review seem to confirm the safety and feasibility of LLR for HCC as well as its superiority to OLR according to perioperative outcomes.